STANDAR PELAYANAN KENYAMANAN ANGKUTAN UMUM: ANALISIS PASAL 141 AYAT (1) HURUF C UNDANG-UNDANG NOMOR 22 TAHUN 2009 TENTANG LALU LINTAS DAN ANGKUTAN JALAN - Afifah Endah Rahayu; Zainal Arifin; Wachid Hasyim (Legal Standing : Jurnal Ilmu Hukum, 2023)
Land transportation operating in Indonesia must meet the technical and road-worthy requirements according to Law Number 22 of 2009 concerning Road Traffic and Transportation. Means of transportation/vehicles, before operating must meet the standards of whether the vehicle is suitable for use when driving on the road and provide a sense of security and comfort. In fact, there are still several cases of vehicles operating on the road that have not fully provided passengers with a sense of security and comfort while traveling, because they do not comply with regulations. The purpose of this study is to analyze the Application of Law Number 22 of 2009 concerning Road Traffic and Transportation in the Tulungagung Regency Area, Case Studies at Gayatri Terminal Type A. This type of research uses field research (Field Research) using an applied legal approach (normative empirical). . Sources of research data are primary and secondary data. Methods of data collection using documents, literature studies, information from informants. Analysis of research data using qualitative normative analysis. The Tulungagung Regency Transportation Service has implemented the existing provisions properly. As for the obstacles in its implementation, it was found that convenience support facilities could not be realized, namely the absence of seat numbers or seat numbers on some public transportation.